Production of clovamide and its analogues in Saccharomyces cerevisiae and Lactococcus lactis. (1st September 2019) - Bouchez, P.; Teixeira Benites, V.; Baidoo, E.E.K.; Mortimer, J.C.; Sullivan, M.L.; Scheller, H.V.; Eudes, A.
Abstract: Clovamide and its analogues are N ‐hydroxycinnamoyl‐L‐amino acids (HAA) that exhibit antioxidant activities. For environmental and economic reasons, biological synthesis of these plant‐derived metabolites has garnered interest. In this study, we exploited HDT1, a BAHD acyltransferase recently isolated from red clover, for the production of clovamide and derivatives in S . cerevisiae and L . lactis . HDT1 catalyses the transfer of hydroxycinnamoyl‐coenzyme A (CoA) onto aromatic amino acids. Therefore, by heterologously co‐expressing HDT1 with 4‐coumarate:CoA ligase (4CL), we succeeded in the biological production of clovamide and more than 20 other HAA, including halogenated ones, upon feeding the engineered micro‐organisms with various combinations of cinnamates and amino acids. To the best of our knowledge, this is the first report on the biological synthesis of HAA and, more generally, on the synthesis of plant‐derived antioxidant phenolic compounds in L . lactis . The production of these health beneficial metabolites in Generally Recognized As Safe (GRAS) micro‐organisms such as S . cerevisiae and L . lactis provides new options for their delivery as therapeutics. Significance and Impact of the Study: N ‐hydroxycinnamoyl‐L‐amino acids such as clovamide are bioactive plant‐derived phenolic compounds with health beneficial effects. Relying on chemical synthesis or direct extraction from plant sources for the supply of these valuable molecules poses challenges to environmental sustainability. As an alternative route, this work demonstrates the potential for biological synthesis of N ‐hydroxycinnamoyl‐L‐amino acids using engineered microbial hosts such as Saccharomyces cerevisiae and Lactococcus lactis . Besides being more eco‐friendly, this approach should also provide more structurally diverse compounds and offer new methods for their delivery to the human body.